PERSEPSI KEPALA SEKOLAH DAN PESERTA DIDIK TERHADAP KINERJA GURU PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN DI SMAN SE- KABUPATEN BENGKAYANG - Devisko, Devisko; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractDevisko (2017). Perceptions of Principals and Students on Teacher Performance Penjasorkes At State Senior High School Bengkayang Regency. Advisor: Mimi Haetami, M.Pd, and Andika Triansyah, M.Or. Problems In This Study Is How Big The Perception Of Principals And Students To The Performance Of Penjasorkes Teachers. Aim For Mapping Perceptions Of Principals And Students Of Teachers Of The Orchestra At High School Of State In Bengkayang Regency.The method of this research is quantitative descriptive method with survey form. The population of 24 principals and 4915 students and sampling using purposive sampling technique with the number of sample 17 principals and 283 students. Conclusions in this study is the perception of principals and learners on the performance of teacher penjasorkes in Bengkayang district can be stated that the performance of teacher penjasorkes in Bengakayang District is Good.Keywords: Perception and Performance Â